# Become Friends With Logarithms Logarithms are actually very easy once you get used to how they

behave. After that they are as predictable as yesterday’s weather. All it takes is practice. What is a logarithm? A logarithm is an exponent. Specifically, logarithms are written “ log b x = y ” and read as “the log, base b, of x is y”. It really means “base b, taken to the power y, gives x”. Hence,
log b x = y ⇔ b y = x

So, for instance, if you had an unknown variable as an exponent, you’d work out a logarithm to find that exponent’s value. Here’s an easy example: 2 x = 8 . In this case we know from past experience that x = 3, since 2 3 = 8 . Hence, “3 is the logarithm, base 2, of 8”, or 3 = log 2 8 . • Practice Set I – Converting from exponential into logarithm form.

In this set, you take a known expression that should be obviously true, and convert it into its equivalent logarithm form. This will give you practice to see where the proper places are for each number in the logarithm form. Example: Given 4 2 = 16 , you’d rewrite this as log 4 16 = 2 .
2 4 = 16 32 = 9 10 3 = 1000 251 / 2 = 5 10 − 2 = 0.01 •

5 3 = 125 70 = 1 81 / 3 = 2 2 −1 = 3 −3 =
1 2 1 27

Practice Set II – Converting from logarithm form back into exponential form.

Now we go backwards, so to speak. Convert these true logarithms back into their equivalent exponential format. At first you may not see that each given logarithm is true, but if you rewrite it as the more familiar exponential form, hopefully this will help you see how logs are properly written.

Example: log 6 36 = 2 is a true logarithm statement. Trust me. If you rewrite this as 6 2 = 36 , perhaps you will agree now, too.
log 2 32 = 5 log 5 25 = 2 log10 10 = 1 log 9 81 = 2 log 16 4 = log 6 1 = 0
1 2

log 2 1 4 = −2 log 49 7 = log 8 2 =
1 3 1 2

© Scott Surgent – ASU Mathematics

of course). we apply a logarithm. But. you know that 2 3 = 8 . In this case. you have logarithms that seem to have all the right numbers but they are in the wrong places. Literally translated into exponentials. “Bases cancel logs”.• Practice Set III – Find the error! In this set. and leaves x all by itself. © Scott Surgent – ASU Mathematics . These are both true. Note: Square roots are equivalent to the 1 2 power. For 1 example. and so forth. Many =1 3.3 9 people stumble on these because they may have forgotten the basic rules of exponents. Also recall that negative powers act as reciprocals. You may have to rewrite back into exponential form.001 = log x 1 125 = −3 Note: In many books you will often see expressions like log 4 16 . Determine its value. if we need to “undo” a logarithm. Equivalently. re-arrange into exponential form and see if that helps. This leads to a handful of useful properties: (Remember. just as squares and square roots undo one another. this would read as 2 8 = 3 . so the corrected logarithm should be log 2 8 = 3 log 5 2 = 25 log 4 0 = 1 log 64 8 = 2 • log 25 1 2 =5 log 7 1 = 7 log 4 (−1) = log 3 3 = 27 1 4 log10 2 = 100 log 3 5 = 125 Practice Set IV – Find the Unknown. base b is always positive and ≠ 1) log b b x = x . which implies x = 2. In this case simply set it equal to a variable x and perform the steps as in the above set. In each logarithm is an unknown value x. b log b x = x . we apply an exponential (usually we just re-write as an exponential). which is not equal to 3. Rewrite as 7 x = 49 . if we need to “undo” an exponential. This is a restatement of the above property. the “ log b ” cancels the base b. et cetera. In algebra. Logarithms and exponentials “undo” one another. log 5 5 = 1 2 and log 6 36 = −2 . but with practice you should be able to determine x without having to do this middle step. You must re-arrange them so that the logarithm is corrected. Do you see why? If not. so that 3 = 1 . which is obviously false (2 to the 8th power is 256. log x 25 = 2 log 6 x = 2 log 8 64 = x log 4 2 = x log 3 x = −1 log 9 1 = x log12 x = 1 log10 0. Example: log 2 3 = 8 is incorrect. You now have log 4 16 = x . Example: log 7 49 = x . cube roots are equivalent to the −1 −2 1 3 power.

 4x 2 y  2 1/ 2 Example: Expand log 2   z   .Properties. • Practice Set V – Expansions of Logarithms. Algebraic properties of logarithms. It is a corollary of the first property. log 2 4 = 2 ) to get 2 + 2 log 2 x + log 2 y − 1 2 log 2 z Try these: log 3 (9 xy 2 ) log 4 ( xy 2 z )  x  log 5   25 y      100 x 2  log  y3     2 log 6 (6 x y ) 3  10( x − 1) 2  log  yz 2     © Scott Surgent – ASU Mathematics . log b   y  = log b x − log b y   III . we note a couple of conventions: “log” without a base written is understood to be log 10 . log b 1 = 0 . for all bases b. I . By Rule I we can break up the first term and get log 2 4 x 2 y − log 2 z 1 / 2 = log 2 4 + log 2 x 2 + log 2 y − log 2 z 1 / 2 . continued. we have log 2 4 x y − log 2 z (Do you see where the   ½ power of z came from?). and simplify the first term (remember. There are three. and you must know these. “ln” is shorthand for the natural logarithm. This is true because b 0 = 1 for all bases b. By rule II. Rewrite into exponential form and this will be obvious. which is the log e . log b x n = n log b x All three properties have to do with how exponents behave when you multiply or divide terms with a common base. Lastly. This is how you actually manipulate logarithms as an algebraic operation. log b ( xy ) = log b x + log b y x II . log b b = 1 . Now we can apply Rule III.

Use other rules of normal algebra as you see fit. You can essentially figure the answer by some educated guesses. use rule III and use the change-of-base rule to get our result. it can be any base): log 2 x = log 6 Use rule III to bring down the exponent: x log 2 = log 6 .. By rule II we can bring up the coefficients and turn them into powers and get 3 + log 2 x 2 + log 2 y − log 2 z . By rules I and II we get log 2   z    1 2 2 log 3 x + 3 log 3 y − log 3 z 1 + log 4 x − 1 2 log 4 y 2(log x + 3 log y ) − 5 log z • (log 2 x − (2 log 2 y + 3 log 2 z )) + log 3 x − 2 log 3 y + 3 log 3 z 2 + log x − log y − 2 log z 1 3 Practice Set VII – Algebra With Logarithms In the equation 2 x = 8 . = 6. it’s pretty obvious that x = 3. get the x down from its perch...• Practice Set VI – Contraction of Logarithms Now go the other way – combine these individual logs into one big logarithm! Example: 3 + 2 log 2 x + 1 2 log 2 y − log 2 z . What about the case of 2 x = 6 ? In this case we use logarithms to “undo” the exponential – i. We take logarithms of both sides. Recall that 3 = log 2 8 and we have log 2 8 + log 2 x + log 2 2  8x 2 y  ..00015 . . 3x = 7 5 x = 12 42x = 9 2(3 x ) = 12 1+ 2x = 8 7 x + 2 = 20 5 2 x +3 = 15 1 + 4(2 x +1 ) = 10 2 x +1 = 3 x 5 x +1 + 2 = 12 8 x = 16 10 4 x −3 = 1.e. y − log 2 z .000 © Scott Surgent – ASU Mathematics .585 log 6 log 2 ≡ 2. which is close enough.585. Divide by log 2 and we get x = Check: 2 2. Example: Solve 2 x = 6 Take logs of both sides (just log will do.

The expression u is ௨ ௗ௫ ଵ ௗ௨ Example: Find the derivative of ‫ = ݕ‬ln(‫ ݔ‬ଶ + 3‫ ݔ‬− 5). or more simply as ‫ ݕ‬ᇱ = మ . ሾln ‫ݑ‬ሿ = ∙ . the derivative is found by differentiating each of ଶ ௫ మ (ଷ௫ିଵ) ௫ మ (ଷ௫ିଵ) − ௫ ఱ ା଻.• Practice Set VIII – (Calculus) Differentiation of Logarithm Functions ௗ௫ ௗ The basic derivative form is called the argument.01 = −2 Set II log 2 32 = 5 ⇒ 2 5 = 32 log 5 25 = 2 ⇒ 5 2 = 25 log10 10 = 1 ⇒ 101 = 10 5 3 = 125 ⇒ log 5 125 = 3 7 0 = 1 ⇒ log 7 1 = 0 81 / 3 = 2 ⇒ log 8 2 = 1 / 3 2 −1 = 1 2 ⇒ log 2 3 −3 = 1 27 1 2 = −1 = −3 ⇒ log 3 1 27 log 9 81 = 2 ⇒ 9 2 = 81 1/ 2 log16 4 = 1 =4 2 ⇒ 16 −2 log 2 1 = 4 = −2 ⇒ 2 1 4 1/ 2 log 49 7 = 1 =7 2 ⇒ 49 1/ 3 log 8 2 = 1 =2 3 ⇒8 log 6 1 = 0 ⇒ 6 0 = 1 © Scott Surgent – ASU Mathematics . The individual smaller logarithms are then easier to differentiate. Using the above form. Therefore. these smaller logarithms: ‫ ݕ‬ᇱ = + ௫ Example: Find the derivative of ‫ = ݕ‬ln ቀ ఱ ቁ. we have ‫ ݕ‬ᇱ = ଵ ଶ௫ାଷ ∙ (2‫ ݔ‬+ 3). ଷ௫ିଵ ଷ ହ௫ ర Find the derivatives: ‫ = ݕ‬ln(5‫ ݔ‬+ 2) ‫ = ݕ‬ln(‫ ݔ‬ସ + 2‫ ݔ‬ଶ + 5) ‫ = ݕ‬ln(݁ ଶ௫ + 7) ‫ = ݕ‬ln൫‫ ݔ‬ଶ √3‫ ݔ‬+ 1൯ ‫ = ݕ‬ln ቀଶ௫ య ିହቁ ௫ర ‫ = ݕ‬ln ቀ௘ మೣ (௫ ర ାଵ)ቁ ଻௫ మ √ହ௫ାଵ Answers: Set I 2 4 = 16 ⇒ log 2 16 = 4 3 2 = 9 ⇒ log 3 9 = 2 10 3 = 1000 ⇒ log10 1000 = 3 251 / 2 = 5 ⇒ log 25 5 = 1 / 2 10 − 2 = 0.01 ⇒ log10 0. Expand this logarithm: we have ln ቀ ఱ ቁ= ௫ ା଻ ௫ ା଻ ହ 2 ln ‫ ݔ‬+ ln(3‫ ݔ‬− 1) − ln(‫ ݔ‬+ 7). where u is some function of x. మ ௫ ାଷ௫ିହ ௫ ାଷ௫ିହ Use logarithm properties (Practice Set V) to “break apart” a complicated argument.

Set III log 5 2 = 25 ⇒ log 5 25 = 2 log 4 0 = 1 ⇒ log 4 1 = 0 log 64 8 = 2 ⇒ log 8 64 = 2 log 25 1 2 = 5 ⇒ log 25 5 = 1 / 2 log 7 1 = 7 ⇒ log 7 7 = 1 log 4 (−1) = 1 4 ⇒ log 4 1 4 log10 2 = 100 ⇒ log10 100 = 2 log 3 5 = 125 ⇒ log 5 125 = 3 = −1 log 3 3 = 27 ⇒ log 3 27 = 3 Set IV log x 25 = 2 ⇒ x = 5 log 6 x = 2 ⇒ x = 36 log 8 64 = x ⇒ x = 2 log 4 2 = x ⇒ x = 1 / 2 log 3 x = −1 ⇒ x = 1 / 3 log 9 1 = x ⇒ x = 0 log12 x = 1 ⇒ x = 12 log10 0.001 = x ⇒ x = −3 log x 1 125 = −3 ⇒ x = 5 Set V  100 x 2  log  y3   = 2 + 2 log x − 3 log y   2 log 6 (6 x y ) 3 = 3(1 + 2 log 6 x + log 6 y )  10( x − 1) 2 log  yz 2     = 1 + 2 log( x − 1) − log y − 2 log z  log 3 (9 xy 2 ) = 2 + log 3 x + 2 log 3 y log 4 ( xy 2 z ) = log 4 x + 2 log 4 y + 1 2 log 4 z  x  log 5   25 y   = log 5 x − 2 − log 5 y   Set VI  x2 ⋅ y3  2 log 3 x + 3 log 3 y − log 3 z = log 3   z      4⋅ x    1 + log 4 x − 1 2 log 4 y = log 4   y   (x ⋅ y ) 2(log x + 3 log y ) − 5 log z = log z5 1 2 3 2 (log 2 x − (2 log 2 y + 3 log 2 z )) = log 2 x y ⋅ z3 2  100 ⋅ x  2 + log x − log y − 2 log z = log  y ⋅ z2      3 3 ⋅ x ⋅ z3  1   + log x − 2 log y + 3 log z = log 3 3 3 3 3  y2   © Scott Surgent – ASU Mathematics .

792 2(3 x ) = 12 ⇒ x = 1.4605 5 2 x +3 = 15 ⇒ x = −0.807 7 x + 2 = 20 ⇒ x = −0.000 ⇒ x = Set VIII ‫ݕ‬ᇱ = ହ௫ାଶ ସ௫ య ାସ௫ ହ ‫ ݕ‬ᇱ = ௫ ర ାଶ௫ మ ାହ ‫ݕ‬ᇱ = ௘ మೣ ା଻ ௫ ଶ ସ ଶ ଶ(ଷ௫ାଵ) ଺௫ మ ହ ଷ ଶ௘ మೣ ‫ݕ‬ᇱ = + ‫ ݕ‬ᇱ = ௫ − ଶ௫ య ିହ ‫ ݕ‬ᇱ = ௫ + ଶ(ହ௫ାଵ) − 2 − ௫ ర ାଵ ସ௫ య If you see an error.431 8 x = 16 ⇒ x = 4 3 3 2 10 4 x −3 = 1.659 1 + 4(2 x +1 ) = 10 ⇒ x = 0.edu Updated 12/12/2012 © Scott Surgent – ASU Mathematics .Set VII 3 x = 7 ⇒ x = 1.771 5 x = 12 ⇒ x = 1. please email: surgent@asu.631 1 + 2 x = 8 ⇒ x = 2.709 5 x +1 + 2 = 12 ⇒ x = 0.1699 2 x +1 = 3 x ⇒ x = 1.544 4 2 x = 9 ⇒ x = 0.